Identification of total suspended solid (TSS) in the Aceh waters from ocean color. Issue 1 (May 2021) - Syawani, U; Haditiar, Y; Ikhwan, M; Wafdan, R; Muhammad, M; Setiawan, I; Jalil, Z; Chaliluddin, M A; Rizal, S
Abstract: The suspended sediment in Aceh waters was analysed from remote Sensing Reflectance of Aqua MODIS resolution 4 km. Two equations from previous studies were used to determine the magnitude and distribution of suspended sediment concentrations in Aceh waters during 2018. The results show the suspended sediment concentrations from the two equations are relatively the same even though they differ spatially (offshore and near the coast of Aceh waters). Based on Zhan et al. equation, the suspended sediment in Aceh waters have a maximum value of 0.786 mg/L and a minimum value of 0.589 mg/L. Meanwhile, based on Zhang et al. equation, the maximum and minimum suspended sediment in Aceh Waters are 0.639 mg/L and 0.271 mg/L, respectively. Based on these two equations, Krueng Kluet estuary located in the western part of Aceh has the highest suspended sediment. In contrast, Krueng Peusangan estuary in the eastern part of Aceh has a low sediment concentration. The highest suspended sediment in Aceh waters occurs in November to December and the low period is in April to September. The heavy rainfall encourages freshwater runoff and high suspended sediment in the mouth of the Aceh waters, especially in the western part of Aceh.